Acceptability of oral HIV self-testing among female sex workers in Gaborone, Botswana - Shava, Emily; Bärnighausen, Till (PLOS ONE, 2020)
Background HIV prevalence among female sex workers (FSW) in sub-Saharan Africa is much higher than in the general population. HIV self-testing (HIVST) may be useful for increasing testing rates in FSW. Methods We conducted semi-structured in-depth interviews among FSW, nurses and lay counsellors providing services to FSWs in Botswana. We aimed to gain understanding of perceived acceptability, anticipated barriers, and preferred approaches to HIVST among FSW. Interviews were audio-recorded, transcribed and translated. Transcripts were reviewed and coded independently by two investigators; high inter-coder agreement was achieved (Kappa = 0.80). Results We interviewed five care providers whose average age was 40 years (SD = 2,64, range = 37-43); three nurses and two counsellors. Thirty FSW were interviewed, with mean age 34 years (range = 20-52). Most (27; 90%) FSW expressed great interest in using HIVST kits. Facilitators of HIVST were: awareness of own risky sexual behaviours, desire to stay healthy, and perceived autonomy over one’s healthcare decisions. Perceived advantages of HIVST included convenience, privacy, and perception of decreased stigma. Identified barriers to HIVST included lack of knowledge about the HIVST kit, fear of testing due to anticipated stigma, mistrust of the test’s accuracy, doubt of self-competency to perform HIVST, and concerns about not linking to care. Assisting someone to test was noted as good for providing emotional support, but there were concerns about confidentiality breaches. Providers expressed concerns over low literacy among FSWs which could affect comprehension of testing instructions, and competency to perform testing and interpret results. Participants’ recommendations for implementation of HIVST included: ensuring wide dissemination of information on HIVST, engaging peers in information-sharing and education, making test kits accessible in FSW-friendly centres, and having clear instructions for linkage to healthcare and support. Conclusion HIVST shows high acceptability among FSWs in Gaborone Botswana, with providers expressing some concerns. Implementation should be peer-driven with healthcare provider oversight.
Gesehen am 23.10.2020